Real-time Impact Evaluation of a Capacity-Building Health Project in Lao PDR - 이계우 (14383, 2015)
This study presents a real-time impact evaluation of a human capacity building health project in Laos, financed by a Korean aid agency and executed jointly by Laotian and Korean higher educational agencies. The project aims to improve the health status of